Mitigación de Contaminantes Físicos y Químicos en el Acceso Vehicular de la Facultad CAREN. - Chanaguano Cocha, Ana Rocío (2019)
of the Faculty CAREN has allowed the creation of new access roads for better mobility. However, there was to generate pollutants possible following the execution of road work. This research aimed to reduce the environmental impact of partner physical and chemical contaminants in vehicle access Faculty CAREN. early assessments of the sources of physical and chemical (PM2.5 and PM10) issued by the fleet pollutants (noise) and were performed. Data were obtained by using equipment to noise sound level meter (Digital class II) to the E-BAM PM (particle sizer with beta ray attenuation). Noise levels compared to TULSMA Book VI Annex 5 exceed the maximum permissible limits (maximum 79,7dB)> (45dB). Concentrations of particulate PM10 and PM2.5 are within the maximum allowable limits in 24 hours according to Annex VI TULSMA Paper 4 (PM2.5 = 11,68ug / m3) <(150 ug / m3), (PM10 = 46ug / m3) <(250 ug / m3) and Guidelines Air Quality and (PM2.5 = 11,95ug / m3) <(20 ug / m3), (PM10 = 46ug / m3) <(50ug / m3 ). However, they consider the peak hours of highest concentration PM (PM2.5 (38ug / m3) to 0800) and (PM10 (143 ug / m3) to 13H00). Identification of native flora was made according to the living area of Ceypsa (dry forest Montano - Low between 2,200 - 3,000 m). They were identified 7 tree species molle (Schinus molle), pumamaqui (Oreopanax ecuadorensis), alder (Alnusa cuminata), guava (Inga insignis), walnut (Juglans Neotropica), gooseberries (Prunus serotina), quishuar (Buddleja bullata) and 6 shrubs guarango (Caesalpinia spinosa), ragwort (Baccharis latifolia), dairy (Euphorbia laurifolia), iguilian (Monnina obtusifolia), laurel wax (Morella pubescens), false snuff (Nicotiana glauca). These ecosystem services have regulatory protection as local climate, preventing erosion, soil fertility and other services such as food, medicinal resources, habitat for species etc. The proposed measures and activities such as reforestation responsible detailing the campaign "Share your Auto", set a speed limit, use of the car horn responsibly etc. In order to counteract the physical and chemical pollutants in vehicle access. lima local, prevención de la erosión, fertilidad del suelo y otros servicios como alimentos, recursos medicinales, hábitat para especies etc. En la propuesta se detalla las medidas y actividades como la reforestación responsable, la campaña “Comparte tu Auto”, fijar un límite de velocidad, el uso de la bocina del auto de manera responsable etc. Con el fin de contrarrestar los contaminantes físicos y químicos en el acceso vehicular.